MEANING EQUIVALENCE IN THE TRANSLATION OF IDIOMS FROM ENGLISH TO INDONESIAN USING ‘GOOGLE TRANSLATE’ - Susiyati, Susiyati (JOEL: Journal of Educational and Language Research, 2022)
There are many difficulties that a translator might face in translating idioms from Indonesian to English. Besides idioms contains figurative meaning, they have choice of words and collocations which differ from one language to another. The difference is influenced by the culture where the language is used. The objective of this research is to know how ‘Google Translate’ application can translate idioms from Indonesian to English. The writer applies qualitative descriptive research, library research and content analysis to analyze the data. The result of the research shows that 13.33% idioms in Indonesian which are translated into English using “Google Translate” application have equivalent forms and meanings, 3.33% have equivalent form, but nonequivalent meaning, 20% of idioms have nonequivalent forms, but equivalent meanings, and 63.33% have nonequivalent forms and meanings.